Molecular understanding of the interaction of amino acids with sulfuric acid in the presence of water and the atmospheric implication. (November 2018) - Ge, Pu; Luo, Gen; Luo, Yi; Huang, Wei; Xie, Hongbin; Chen, Jingwen; Qu, Jingping
Abstract: Amino acids are important components of atmospheric aerosols. Despite the diversity of amino acids structures, however, the role of amino acids with additional non-characteristic functional groups in new particle formation (NPF) has almost remained unexplored. Herein, the interaction of serine (Ser) and threonine (Thr), which feature a hydroxyl group and differ by a methyl-substitution, with sulfuric acid (SA) and up to three water (W) molecules has been investigated at the M06-2X/6-311++G (3df, 3pd) level of theory. The effects of structural differences of amino acids on the structure and properties of clusters were also pointed out. Results show that serine may play more important role in stabilizing sulfuric acid to promote NPF in initial steps compared with threonine, glycine and alanine. Meanwhile, threonine may participate in ion-induced nucleation due to the high dipole moment of (Thr) (SA) isomers. Moreover, the effects of structure differences of amino acids can be seen in several aspects. Firstly, methyl substitution and hydroxyl group of amino acids have great influence on the structure of clusters. Secondly, hydrated (Ser) (SA) and (Tur) (SA) clusters could retain water even at low relative humidity, which may due to the hydroxyl group in serine and threonine. In addition, the Rayleigh light scattering intensities of amino acid-containing clusters are higher than trimethylamine, monoethanolamine and oxalic acid-involved counterparts. The effect of carboxyl group and methyl substitution on optical properties of clusters is also discussed. This study may bring new insight into the role of amino acids with additional non-characteristic functional groups in initial steps of NPF. Graphical abstract: Image 1 Highlights: Structural differences of amino acids have great influence on cluster structures. (Thr) (SA) clusters may participate in ion-induced nucleation. Serine may play more important role in stabilizing sulfuric acid. Hydrated (Ser) (SA) and (Tur) (SA) clusters could retain water even at low RH. Amino acid clusters possess stronger Rayleigh light scattering intensities.